Optimal site selection for utility-scale solar PV projects using a RETscreen-AHP-TOPSIS framework: application to the southern Cameroon - Yvan Ayuketah; Milton Edimu; Cosmas Mwikirize (Sustainable Energy Research)
Abstract Several countries have renewable energy portfolios aimed at reducing energy sector emissions while diversifying their generation mixes. A cornerstone in these global portfolios is solar photovoltaics (PV) which offer a mature and rapidly deployable solution. Selecting optimal sites for utility-scale solar PV projects remains a complex challenge, requiring the integration of technical, economic, environmental and social criteria. This study proposes a hybrid decision-making framework that embeds financial viability metrics such as net present value (NPV) and greenhouse gas (GHG) emissions savings into multi-criteria analysis. The framework integrates RETScreen Expert for technoeconomic evaluation, the analytical hierarchy process (AHP) for criteria weighting, and the Technique for Order Preference by Similarity to Ideal Solutions (TOPSIS) for ranking alternatives. Applied to fourteen locations in the Southern Interconnected Grid in Cameroon, the model considers a hypothetical 10MW grid-connected solar PV plant. Results identify Baffousam as the optimal location due to its higher solar potential, favorable land use, and grid proximity. Sensitivity analysis reveals the influence of subjectivity weighting in AHP, with land use criterion contributing significantly to site selection, underscoring the need for stakeholder engagement. By bridging traditional energy planning tools (RETScreen) with MCDM techniques, this study addresses a critical gap in existing frameworks which often neglect the time value of money and financial viability. The modular design allows adaptation to regional priorities, offering policy makers and investors a replicable blueprint for emerging economies. This approach advances sustainable energy transitions while balancing technical, economic, and environmental priorities in site selection.